The remarkable Ponto-Caspian amphipod diversity of the lower Durso River (SW Caucasus) with the description of Litorogammarus dursi gen. et sp. nov. - Marin, Ivan; Palatov, Dmitry; Copilaș-Ciocianu, Denis (Zootaxa, 2023)
The first insight into the unexpectedly diverse amphipod assemblage of the Durso River (Novorossiysk area) in the SW mountainous pre-Caucasian area is presented. The presence of six species is revealed, including three new records for the area and one species new to science. The phylogenetic relationships of all studied species and their relatives were examined based on the divergence of the COI mtDNA gene marker (barcoding). The conducted research clearly showed that the coastal part of the Black Sea and the adjacent pre-Caucasian river/land areas harbors a significant undescribed diversity, and that the transitional sea/river brackish biotopes are important reservoirs of the endemicity. A new genus, Litorogammarus gen. nov. is proposed for native pebble-dwelling species, namely Echinogammarus karadagiensis Grintsov, 2009, Echinogammarus mazestiensis Marin & Palatov, 2021 and the newly discovered Litorogammarus dursi sp. nov., from the lower (estuarine) part of the Durso River and adjacent coastal areas. These three species form a strongly supported molecular clade and share a number of characters such as smooth body without carinae and setae, antenna II armed with dense curled setae, lacking calceoli, pereopods III–VII with sparse, short setation, epimeral plates armed with spines only, telson lobes longer than broad, gradually tapering, bearing only spines. Pectenogammarus oliviiformis (Greze, 1985) comb. nov. is also discovered in the area and is re-described herein. Although this is probably one of the most abundant and common coastal pebble-dwelling species along the northeastern coasts of the Black Sea, it was previously poorly described and thus overlooked by researchers.